Oxygen Spectroscopy and Polarization-Dependent Imaging Contrast (PIC)-Mapping of Calcium Carbonate Minerals and Biominerals - DeVol, R.; Metzler, R.; Kabalah-Amitai, L.; Pokroy, B.; Politi, Y.; Gal, A.; Addadi, L.; Weiner, S.; Fernandez-Martinez, A.; Demichelis, Raffaella; Gale, Julian; Ihli, J.; et al. (American Chemical Society, 2014)
X-ray absorption near-edge structure (XANES) spectroscopy and spectromicroscopy have been extensively used to characterize biominerals. Using either Ca or C spectra, unique information has been obtained regarding amorphous biominerals and nanocrystal orientations. Building on these results, we demonstrate that recording XANES spectra of calcium carbonate at the oxygen K-edge enables polarization-dependent imaging contrast (PIC) mapping with unprecedented contrast, signal-to-noise ratio, and magnification. O and Ca spectra are presented for six calcium carbonate minerals: aragonite, calcite, vaterite, monohydrocalcite, and both hydrated and anhydrous amorphous calcium carbonate. The crystalline minerals reveal excellent agreement of the extent and direction of polarization dependences in simulated and experimental XANES spectra due to X-ray linear dichroism. This effect is particularly strong for aragonite, calcite, and vaterite. In natural biominerals, oxygen PIC-mapping generated high-magnification maps of unprecedented clarity from nacre and prismatic structures and their interface in Mytilus californianus shells. These maps revealed blocky aragonite crystals at the nacre-prismatic boundary and the narrowest calcite needle-prisms. In the tunic spicules of Herdmania momus, O PIC-mapping revealed the size and arrangement of some of the largest vaterite single crystals known. O spectroscopy therefore enables the simultaneous measurement of chemical and orientational information in CaCO3 biominerals and is thus a powerful means for analyzing these and other complex materials. As described here, PIC-mapping and spectroscopy at the O K-edge are methods for gathering valuable data that can be carried out using spectromicroscopy beamlines at most synchrotrons without the expense of additional equipment.